Development of the phase composition and the properties of Ti2AlC and Ti3AlC2 MAX-phase thin films – A multilayer approach towards high phase purity - Torres C. (2021)
MAX phase thin films have been synthesized by thermal treatment of a Ti-Al-C multilayer system. The preparation of the multilayer system was carried out via magnetron sputtering. Based on the thickness ratio among the individual nanoscale monolayers (Ti, Al, C), the resulting MAX phase stoichiometry can be controlled. This paper describes the synthesis of both Ti2AlC and Ti3AlC2 MAX phases from the same precursor multilayer system which is composed of a sequence of Ti/Al/C pure elemental single layers with thicknesses of 14, 6, and 3.5 nm, respectively. This sequence is repeated 22 times with a total thickness of around 500 nm. Rapid thermal treatment tests were performed to study the phase development. The Ti2AlC MAX phase forms in a temperature range below 850 °C, whereas the Ti3AlC2 MAX phase starts to form at temperatures above 850 °C and reaches its highest phase purity at 950 °C. The thin film structures were studied by X-ray diffraction and Raman spectroscopy. Furthermore, the electrical and mechanical properties were investigated to gain more insights regarding the phase transformation and their influence on the thin film properties. © 2020 Elsevier B.V.